The Implementation Challenges of Health Information Systems in Iran's Southeastern Hospitals: From Managers' Perspective - Reza Abbasi; Fatemeh Rangraz Jeddi; Shima Anvari; Reza Khajouei (Tehran University of Medical Sciences, 2022)
Background and Aim: Hospital managers are one of the key decision-makers in the implementation of health information systems. This study aimed to determine the implementation challenges of health information systems based on the hospital managers' perspective. Materials and Methods: This descriptive-analytical study was conducted in 2019 on the hospital managers of three provinces (Kerman, Yazd, Sistan and Baluchestan). Data were collected using a self-administrated questionnaire. The face validity of this questionnaire was approved by experts in health informatics and health information management and its reliability was confirmed by Cronbach's alpha (α=96.7%). Data were analyzed using SPSS. To investigate the relationship between the mean of each challenge with demographic variables, Pearson, Independent T-test, and ANOVA tests were used. Results: In this study, the factors related to ignoring the hospital manager's needs in system selection (1.333 out of 2 points), hardware purchase cost, insufficient user training to using the system (1.238), inadequate manpower and health informatics specialists (1.19), software purchase cost, insufficient financial resources (1.142), high cost of system launching, the lack of integration and interoperability among information systems, lack of support from health care professionals (1.047), and lack of management experience in choosing the best system (one out of 2) had the highest scores (out of 2 points). Also, personnel training costs to work with the system (-0.092) and Lack of improvement in work processes (-0.047) obtained the lowest scores. Data analysis showed that managers with clinical backgrounds considered financial and human challenges more important than non-clinical managers (P<0.031). Conclusion: The hospital managers believed that financial, human, technical, managerial, and organizational factors are the most important challenges in implementing health information systems in Iran's hospitals respectively. The health policy-makers and planners at large and small levels can address many of the challenges before implementing systems by focusing on identified priorities.